Clinical Practice of Steroid Avoidance in Pediatric Kidney Transplantation. Issue 8 (23rd April 2015) - Nehus, E.; Liu, C.; Hooper, D. K.; Macaluso, M.; Kim, M.‐O.
<x xml:space="preserve">Abstract</x> Steroid‐avoidance protocols have recently gained popularity in pediatric kidney transplantation. We investigated the clinical practice of steroid avoidance among 9494 kidney transplant recipients at 124 transplant centers between 2000 and 2012 in the Organ Procurement and Transplantation Network database. The practice of steroid avoidance increased during the study period and demonstrated significant variability among transplant centers. From 2008 to 2012, 39% of transplant centers used steroid avoidance in <10% of all discharged transplant recipients. Twenty‐one percent of transplant centers practiced steroid avoidance in 10–40% of transplant recipients, and 40% of transplant centers used steroid avoidance in >40% of discharged patients. Children receiving steroid avoidance more frequently received induction with lymphocyte‐depleting agents. Repeat kidney transplants were the least likely to receive steroid avoidance. Children who received a deceased donor kidney, underwent pretransplant dialysis, were highly sensitized, or had glomerular kidney disease or delayed graft function were also less likely to receive steroid avoidance. The variation in practice between centers remained highly significant (p < 0.0001) after adjustment for all patient‐ and center‐level factors in multivariate analysis. We conclude that significant differences in the practice of steroid avoidance among transplant centers remain unexplained and may reflect uncertainty about the safety and efficacy of steroid‐avoidance protocols.